Using the GenCut core biopsy tool with the radial endobronchial ultrasound guide sheath enables a high‐quality histology sample capable of programmed cell death ligand 1 (PD‐L1) testing. Issue 5 (4th April 2022) - Herath, Samantha; Bashirzadeh, Farzad; Mahajan, Hema; Ing, Alvin; Fielding, David
Abstract: Radial EndoBronchial UltraSound (R‐EBUS)‐guided biopsies are a promising biopsy technique for pulmonary nodules suspected of lung cancer with great safety profile. Programmed cell death ligand 1 (PD‐L1) testing is increasingly demanded from lung biopsies. GenCut is a novel blunt tool that can be used to obtain core biopsies. This case series explores prospective performance of the GenCut core biopsy with R‐EBUS. Once Peripheral Pulmonary Lesion was located, GenCut biopsy was performed followed by conventional (forceps ± cytology brush) R‐EBUS biopsies. The overall diagnostic yield for the 16 patients with a mean peripheral pulmonary lesion (PPL) size of 4.1 cm was 100% from multi‐modal R‐EBUS sampling. The diagnostic yield for GenCut tool alone was 13/16 (81.2%) and the ability to perform PD‐L1 from GenCut was 10/16 (62.5%). There were no adverse events recorded. GenCut tool is a novel blunt instrument that can be used safely to obtain a core biopsy suitable for PD‐L1 in combination with R‐EBUS without compromising the high safety profile. Abstract : Radial EBUS (R‐EBUS)‐guided biopsies are a promising biopsy technique for pulmonary nodules suspected of lung cancer with great safety profile. Programmed cell death ligand 1 (PD‐L1) testing is increasingly demanded from lung biopsies. GenCut is a novel blunt tool that can be used to obtain core biopsies. This case series explores prospective performance of the GenCut core biopsy with R‐EBUS.